Students' Creative Thinking Ability Through the Project Based Learning (PjBL) Model Assisted by Talking Sticks - Sri suryaningsih; Nurwalidainismawati; Nurlailatun Ramdani (Jurnal Elementaria Edukasia, 2024)
Having the ability to think creatively is preparation for facing the 4.0 era. The application of the Project Based Learning model assisted by Talking Stick in science subjects can create an active learning atmosphere, create new ideas, be cheerful and enthusiastic so that it can improve students' creative thinking abilities. This research is a type of quantitative experimental research with a pre-experimental design. The research was conducted in class V at SDN 01 Kaleo, SDN 02 Kaleo, and SD Inpres Kaleo, totaling 69 students. The research instrument uses multiple choice tests and descriptions. Data analysis uses the Actual Completion Limit (BTA). The mastery of students' creative thinking abilities increased by 11.6% from the pre-test of 66.7% to the post-test of 78.3%. After implementing the PjBL model assisted by Talking Stick, the classification of creative thinking abilities increased in the high category. There were no students in the pre-test while there were 14 students in the post-test. The creative thinking abilities of fifth grade students in the science subject water cycle material can increase after implementing the PjBL model with the help of Talking Stick. The development of a PjBL-based textbook with the help of Talking Stick for students' creative and critical thinking abilities is the idea for the development of this research.